Menir de Fontelo (Armamar, Viseu): Primeira notícia - Gomes, Mário Varela; Sousa, Orlando (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2021)
We bring to light the discovery of a new tall menhir, currently laid on the ground, away from its primitive erection site, in Vale de Naçarães, southwest Fontelo village (Armamar, Viseu) allowing some considerations. It is a monolith sculpted with local granitic rock, subcylindrically shaped, but presenting pointed extremities, measuring 5.32 m long and 1.18 m in maximum width. The exposed surface shows three engraved cup-marks, one near the top and two paired on the mesial volume, as well as at the central area four large pecked concentric circles, containing on its inside a fifth circle, smaller and not centred with the larger ones. Other cup-marks were detected, but all the engravings are much eroded and were possibly made when the menhir was already down. This kind of monuments was probably built in the 5th millennium B.C., when the first passage graves appear in the region. The large dimensions of this monolith, when erected allowed his viewing from a far distance thus ordaining the surrounding space. The authors propose that this menhir to be reerected and signalised through explanatory board on his historical and archaeological importance.